2015
DOI: 10.1080/21645515.2015.1084451
|View full text |Cite
|
Sign up to set email alerts
|

Safety and reactogenicity of the combined diphtheria-tetanus-acellular pertussis-inactivated poliovirus-Haemophilus influenzaetype b (DTPa-IPV/Hib) vaccine in healthy Vietnamese toddlers: An open-label, phase III study

Abstract: The introduction of combination vaccines plays a significant role in increasing vaccine acceptance and widening vaccine coverage. Primary vaccination against diphtheria, tetanus, pertussis, poliomyelitis and Haemophilus influenza type b (Hib) diseases has been implemented in Vietnam. In this study we evaluated the safety and reactogenicity of combined diphtheria-tetanus-pertussis-inactivated polio (DTPa-IPV)/Hib vaccine when administered as a booster dose in 300 healthy Vietnamese children <2 years of age (mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 10 publications
1
13
0
Order By: Relevance
“…3 The vaccine administered as a primary and/or booster vaccination has been shown to be well tolerated and immunogenic in infants in previous studies. [4][5][6][7][8][9] Since population-based immune response differences might be observed, [10][11][12][13][14] further studies may be needed to include multivalent vaccines in the National Immunization Programs of different countries. In Korea, three-dose primary vaccination of infants against diphtheria, tetanus, pertussis, poliomyelitis and Hib is recommended by the Korean Pediatric Society at 2, 4 and 6 months of age.…”
Section: Introductionmentioning
confidence: 99%
“…3 The vaccine administered as a primary and/or booster vaccination has been shown to be well tolerated and immunogenic in infants in previous studies. [4][5][6][7][8][9] Since population-based immune response differences might be observed, [10][11][12][13][14] further studies may be needed to include multivalent vaccines in the National Immunization Programs of different countries. In Korea, three-dose primary vaccination of infants against diphtheria, tetanus, pertussis, poliomyelitis and Hib is recommended by the Korean Pediatric Society at 2, 4 and 6 months of age.…”
Section: Introductionmentioning
confidence: 99%
“…38 Some international studies demonstrated the advantages of vaccinations administered in the same visit, such as an increase in vaccination coverage, an increase in compliance with the entire vaccination course and the respect of the correct timing. 9,11,25,26 Kurosky et al 73 show how the combination of vaccines has considerably increased adherence to the complete vaccination course compared to what happens with the administration of monovalent vaccines. For example, as regards MMR vaccination, compliance with the timing of the vaccination course in those who received the combined vaccine was significantly higher (81.4%) compared to those who received the single vaccines (63.4%).…”
Section: Summary Of Product Characteristics (Smpc): Co-administrationmentioning
confidence: 99%
“…There are concerns about the possibility that too many vaccines overload the immune system, that the combined vaccines may be less effective and can cause a greater number of adverse reactions compared to the vaccines administered separately. 10,11 Combined products reduce the number of injections and pain compared to repeated injections; on the other hand, they also reduce cumulative exposure to preservatives and stabilizers that are erroneously linked by hesitant parents to the onset of adverse reactions. 12,13 Furthermore, co-administration reduces the number of visits and, therefore, decreases stress and discomfort for children and parents.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations